2013
DOI: 10.1093/conphys/cot019
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of larval and juvenile white sturgeon to barotrauma: can they handle the pressure?

Abstract: Techniques were developed to determine when fish are vulnerable to barotrauma when rapidly decompressed during hydroturbine passage. Sturgeons were decompressed in early life-stages and X-ray radiographs were taken to determine when gas was present in the swim bladder. Barotrauma was observed on day 9 and greater than 75 days after hatching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…Susceptibility to barotrauma among fish larvae appears to be highly species-specific (Boys et al, 2016), and several studies indicate that there does not appear to be any effects of rapid pressure changes on fish egg viability (Boys et al, 2016;Brown et al, 2013).…”
Section: Pumping Station Factorsmentioning
confidence: 99%
“…Susceptibility to barotrauma among fish larvae appears to be highly species-specific (Boys et al, 2016), and several studies indicate that there does not appear to be any effects of rapid pressure changes on fish egg viability (Boys et al, 2016;Brown et al, 2013).…”
Section: Pumping Station Factorsmentioning
confidence: 99%
“…Brown et al (2013a) noted barotrauma in the form of erratic swimming, death, and herniation-like abnormalities on the abdomen of larval White Sturgeon (Acipenser transmontanus) at the point when they first started feeding (8 days after hatching) but did not have an inflated swim bladder. Brown et al (2013a) noted barotrauma in the form of erratic swimming, death, and herniation-like abnormalities on the abdomen of larval White Sturgeon (Acipenser transmontanus) at the point when they first started feeding (8 days after hatching) but did not have an inflated swim bladder.…”
Section: Implication Of Life History and Behaviormentioning
confidence: 99%
“…Larval drifting fish may also be susceptible to barotrauma due to expansion of metabolically produced gas. Brown et al (2013a) noted barotrauma in the form of erratic swimming, death, and herniation-like abnormalities on the abdomen of larval White Sturgeon (Acipenser transmontanus) at the point when they first started feeding (8 days after hatching) but did not have an inflated swim bladder. They also noted gas in the intestines about 7 months after hatching that could also lead to barotrauma upon decompression.…”
Section: Implication Of Life History and Behaviormentioning
confidence: 99%
“…Larvae from about 25–29 mm showed increased mortality over controls; still larger larvae did not. Brown et al () also found differences in age related injury and mortality in larval and juvenile white sturgeon ( Acipenser transmontanus ) in response to decompression. Barotrauma‐related injuries were first observed at 9‐days post hatch, the same day as initial exogenous feeding.…”
Section: Discussionmentioning
confidence: 93%
“…A number of studies on the effects of pressure changes on fish (i.e., turbine passage, weir passage, cooling condenser passage, underwater detonations) suggest that rapid decompression is the major component of barotrauma (Boys et al, ; Brown et al, , ; Govoni, Settle, & West, ). Injury or mortality is caused by the rapid expansion of gas in organs, such as air in the swim bladder or metabolic gases in the digestive track.…”
Section: Discussionmentioning
confidence: 99%